WOMEN'S LEADERSHIP KEPEMIMPINAN PEREMPUAN DI ERA DIGITAL DALAM PERSPEKTIF SIYASAH SYAR’IYYAH: ANTARA REPRESENTASI SIMBOLIK DAN SUBSTANSI KEPEMIMPINAN - Yoga, Yoga Saputra; Muawan, Muhammad Habib; Kurniati; Rahmiati (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
The development of the digital era has opened up great opportunities for women in public leadership, but often their presence is reduced to symbolic representation that does not touch the substance of power, exacerbated by gender stereotypes and conservative religious interpretations. This study aims to analyze the legitimacy and contribution of women's leadership in the digital era from the perspective of Siyasah Syar'iyyah, positioning it as a contextual managerial and ethical foundation. Using a descriptive qualitative approach through library research, primary data in the form of the Qur'an and classical books and secondary data in the form of relevant books and journals are analyzed through content analysis to connect the principles of Siyasah Syar'iyyah with digital reality. The results of the study conclude that leadership legitimacy is based on the integration of al-quwwah (competence) and al-amanah (integrity) as fundamental managerial values. The transition to substantive leadership is achieved through the implementation of tahqiq al-maslahah (realization of benefits) and mas'uliyyah (accountability), which demands real-time accountability in the digital space. Therefore, the practical implication is the need for digital and political ethics education based on Islamic values ​​to ensure that women's roles are effective and have integrity.